COVID-19 and ophthalmology: is conjunctival transmission possible? - Alexander V. Surov; Ekaterina V. Lyuft; Irina A. Svinareva (Клинический разбор в общей медицине, 2020)
At the end of 2019, an outbreak of a new coronavirus infection occurred in the people's Republic of China with an epicenter in the city of Wuhan (Hubei province). On February 11, 2020, the World Health Organization assigned the official name of the infection caused by the new coronavirus – COVID-19 (Coronavirus Disease 2019). As of May 2020, COVID-19 has been confirmed in nearly three and a half million people and has resulted in just over 230.000 deaths. In January 2020, the first case of death of an ophthalmologist from Wuhan Central hospital who was infected from a patient was recorded, which attracted the attention of the medical community around the world, especially in countries at the center of the pandemic. There are scientific papers showing the possibility of infection with the COVID-19 virus through the mucous membrane of the eye, which is relevant for doctors working in a pandemic, especially practicing ophthalmologists and General practitioners.